Revitalisasi Sampah Organik Menjadi Kompos dan Ecobrik: Upaya Pemberdayaan Komunitas Saka Kalpataru di TPA Banjarsari Trucuk Bojonegoro - Sabilla Putri Khairunisa; Eko Arief Cahyono; Sindy Wahyu Silvia; Ria Ardaniatus Sholikhah; Mira Putri Agestina; Faisal Kusumo (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Waste management continues to be a critical environmental issue, including in Bojonegoro Regency, particularly in the Banjarsari Landfill (TPA) area, Trucuk District. The increasing volume of organic and inorganic waste that has not been managed effectively highlights the urgent need for sustainable waste management strategies involving active community participation. This Community Service Program was conducted to enhance the knowledge, skills, and environmental awareness of Saka Kalpataru Scout members through activities focused on converting organic waste into compost and utilizing plastic waste to produce ecobricks. The program employed the Asset-Based Community Development (ABCD) approach, which emphasizes the utilization of existing community assets, resources, and capacities. The implementation consisted of two main stages: educational sessions on sustainable waste management and practical assistance in composting and ecobrick production, supported by training in basic business management and product marketing. The results of the program indicated a significant improvement in participants’ understanding, as reflected in the increase in the average knowledge score from 45.79 before the training to 76.84 after the training. In addition, 80% of participants reported being highly interested, while 20% stated that they were interested in applying composting and ecobrick production in their daily activities. The program also encouraged greater community participation and transformed participants’ perceptions of waste, which was no longer regarded merely as refuse but as a valuable resource with economic potential. Furthermore, the program contributed to reducing the volume of waste disposed of at the landfill while simultaneously promoting environmental awareness and supporting the development of sustainable green entrepreneurship.